1964
DOI: 10.1002/cjce.5450420602
|View full text |Cite
|
Sign up to set email alerts
|

Minimisation of axial dispersion by use of secondary flow in helical tubes

Abstract: It has Iiwn known for sotnc* tinir that many continuous rhemiriil rrac-tors givr thc. grrutrst ronvrrsion when axial dispersion i* niininiizrd, i.r., whrn plny flow o w n r s . This paprr ronsidrrs the problrni of attaining phig flow in runtinntins flow syktrnik. Thc grunic~triral runfiguration of a tubr wound into 11 helix is wuggrstrd 11s a convrnirnt and rflicirnt tiwans of producing acrondery rurrrnts whirh promotr ~) l i t g flow. On t h r Iisris o f trirrc-r distribution tcsts and prcssnrv drop data it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…They also observed, for laminar flow in helical systems that the effective axial dispersion decreases with an increase in Re due to the secondary flow. However, a transition occurs for Reynolds numbers greater than 3000, for which the strength of the secondary flow becomes less important than axial velocity effects, especially for helical systems with small curvature, thus inducing an increase of the effective dispersion [14]. For still higher Reynolds numbers, the turbulent regime prevails and axial dispersion is reduced by turbulent mixing.…”
Section: Introduction and Literature Surveymentioning
confidence: 92%
“…They also observed, for laminar flow in helical systems that the effective axial dispersion decreases with an increase in Re due to the secondary flow. However, a transition occurs for Reynolds numbers greater than 3000, for which the strength of the secondary flow becomes less important than axial velocity effects, especially for helical systems with small curvature, thus inducing an increase of the effective dispersion [14]. For still higher Reynolds numbers, the turbulent regime prevails and axial dispersion is reduced by turbulent mixing.…”
Section: Introduction and Literature Surveymentioning
confidence: 92%
“…Laminar flow in curved channels of rectangular [ 149,[184][185][186][187][188][189][190]1921 have demonstrated that the secondary flow formed in a curved pipe was a steady helical swirling motion that stabilised the axial flow such that the transitional Reynolds number to turbulent flow (Re,,) exceeded that for straight pipe (Re,,). Spedding and Chen [191] have shown that the elimination of disturbances in the flow or vibration then allowed flow in straight pipe to remain laminar up until Re,,, z 40,000 in contrast to that normally registered, i.e.…”
Section: Curved Pipementioning
confidence: 99%
“…That the secondary flows may reduce dispersion was apparently first recognized a t about the same time by van Andel et al (1964) and Koutsky and Adler (1964), who demonstrated the effect experimentally. Only the gas-phase experiments reported by the first group yielded Gaussian concentration profiles for laminar flow systems, however, so that the corresponding dispersion coefficients were the first reported for curved tubes.…”
Section: Introductionmentioning
confidence: 95%